Cereal fiber intake may reduce risk of gastric adenocarcinomas: the EPIC-EURGAST study. - M A, M; Pera, G; Agudo, A; Bueno-de-Mesquita, H; Palli, D; Boeing, H; Carneiro, F; Berrino, F; Sacerdote, C; Tumino, R; Panico, S; Berglund, G; et al. (2007)
Numerous case-control studies suggest dietary fiber may reduce risk of gastric cancer, but this has not been confirmed prospectively. A previous case-control study reported reduced risk of gastric cardia adenocarcinomas associated with cereal fiber, but not with fruit or vegetable fiber. To date, different food sources of fiber have not been examined with respect to noncardia tumors or diverse histologic sub-types. This study prospectively examines associations between fiber from different food sources and incident gastric adenocarcinomas (GC) among more than 435,000 subjects from 10 countries participating in the European Prospective Investigation into Cancer and Nutrition study. Subjects aged 25-70 years completed dietary questionnaires in 1992-98, and were followed up for a median of 6.7 years. About 312 incident GCs were observed. The relative risk of GC was estimated based on cohort-wide sex-specific fiber intake quartiles using proportional hazards models to estimate hazards ratios (HRs) and 95% confidence intervals (CIs). Intakes of cereal fiber, but not total, fruit or vegetable fiber, were associated with reduced GC risk [adjusted HR for the highest vs. lowest quartile of cereal fiber 0.69, 0.48-0.99]. There was a strong inverse association for diffuse [HR 0.43, 0.22-0.86], but not intestinal type [HR 0.98, 0.54-1.80] tumors. Associations for cardia vs. noncardia tumors were similar to those for overall GC, although cardia associations did not reach significance. Cereal fiber consumption may help to reduce risk of GC, particularly diffuse type tumors. Further study on different food sources of fiber in relation to GC risk is warranted to confirm these relationships.